Tunable Room‐Temperature Synthesis of ReS2 Bicatalyst on 3D‐ and 2D‐Printed Electrodes for Photo‐ and Electrochemical Energy Applications. (8th March 2020) - Ng, Siowwoon; Iffelsberger, Christian; Sofer, Zdenek; Pumera, Martin
Abstract: The advancement in 3D‐printing technologies conveniently offers boundless opportunities for the customization of a practical substrate or electrode for diverse functionalities. ReS2 is an attractive transition metal dichalcogenide (TMD), showing strong photoelectrochemical activities. Two advanced systems are merged for the next step in electrochemistry—the limits of the prevailing synthesis techniques of TMDs operating at high temperature or low pressure, which are not compatible with 3D‐printed polymer electrodes that can withstand only comparatively low temperatures, are overcome. A unique NH4 ReS4 precursor is separately prepared to conduct subsequent ReS2 electrodeposition at room temperature on 3D‐printed carbon and 2D‐printed carbon electrodes. The deposited ReS2 is investigated as a dual‐functional electro‐ and photocatalyst in hydrogen evolution reaction and photoelectrochemical oxidation of water. Moreover, the electrodeposition conditions can be adjusted to optimize the catalytic activities. These encouraging outcomes demonstrate the simplicity yet versatility of TMDs based on electrodeposition technique on a rationally designed conductive platform, which creates numerous possibilities for other TMDs and on other low‐temperature substrates for electrochemical energy devices. Abstract : The combination of two advanced systems for the next step in electrochemistry by room‐temperature synthesis of transition metal dichalcogenide and 3D‐printing of practical electrochemical electrodes is demonstrated. A dual‐functional ReS2 crystal‐like structure is explored as an electro‐ and photocatalyst in hydrogen evolution reactions and photoelectrochemical oxidation of water.